The Influence of Promotion and Price on Purchasing Decisions for Citric Acid Cap Gajah at CV Multi Kimia Internusa - Shafa Kirana; Joko Ariawan (Journal of Current Research In Multidisciplinary, 2023)
This research aims to determine the influence of promotions and prices on purchasing decisions. The method used in this research is a descriptive method with a quantitative approach. The population in this research is made up of customers who have previously purchased the product. This research used the Slovin formula to obtain a sample of 90 respondents. The data analysis techniques used are the validity test, reliability test, classic assumption test of normality, multicollinearity, heteroscedasticity, t-test, f-test, multiple regression analysis test, and determination test using IBM SPSS 21. Calculation results in the t test where the sig value has a partial effect X1 against Y of 0.000 < 0.05 and the t-count value is 7.753 > t-table 1.663. Then calculate the t test, where the sig value partially influences The results of this research show that the promotion and price variables have a significant partial and simultaneous effect on purchasing decisions. By increasing promotional activities and setting the right prices, purchasing decisions will increase.